1994
DOI: 10.1139/h94-013
|View full text |Cite
|
Sign up to set email alerts
|

Rowing Performance and Selected Descriptive, Field, and Laboratory Variables

Abstract: The purpose of this study was to determine the relationships among measures of rowing performance and selected descriptive, field, and laboratory variables. Rowing performance of 20 intercollegiate oarswomen was assessed using a 2,500-m time test on a Concept II rowing ergometer, the rower's competitive experience, and the coach's ranking of the rowers. The oarswomen also underwent standardized descriptive tests including anthropometric measurements, field tests including 90-s rowing ergometer distance and wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 9 publications
4
36
0
1
Order By: Relevance
“…The _ V V O 2max was related to performance (r=0.88, P<0.001), a finding that is in agreement with those of Cosgrove et al (1999;r=0.85) and Kramer et al (1994;r=0.71 Cosgrove et al 1999). Indeed, Steinacker (1993) reported that _ W W 4mmol À1 Table 1 Correlation coefficients for determinants of rowing speed over 2,000 m on the ergometer.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The _ V V O 2max was related to performance (r=0.88, P<0.001), a finding that is in agreement with those of Cosgrove et al (1999;r=0.85) and Kramer et al (1994;r=0.71 Cosgrove et al 1999). Indeed, Steinacker (1993) reported that _ W W 4mmol À1 Table 1 Correlation coefficients for determinants of rowing speed over 2,000 m on the ergometer.…”
Section: Discussionsupporting
confidence: 68%
“…The study of physiological characteristics of high and low performance rowers has revealed that greater maximal oxygen consumption ( _ V V O 2max ) (Secher et al 1983), percentage of slow twitch fibres (Roth et al 1983), body mass (Secher et al 1983) and power output at a blood lactate concentration ([La -] b ) of 4 mmolAEl -1 (Roth et al 1983) are all positively related to performance. Kramer et al (1994) compared several parameters measured in the laboratory and in the field with performance and found that _ V V O 2max was the strongest correlate (r=0.71). Cosgrove et al (1999) examined the relationships between ergometer performance over 2,000 m of rowing and selected physiological variables in club level rowers and reported that _ V V O 2max and lean body mass demonstrated the highest correlation with average velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological responses to simulated rowing races, both in a boat (Di Prampero et al 1971;Jackson and Secher 1976;Secher et al 1983) and on a rowing ergometer (Hagerman et al 1978(Hagerman et al , 1979Kramer et al 1994;Mahler et al 1984;McKenzie and Rhodes 1982;Rosiello et al 1987;Young and Rhodes 1991) have been studied. Subject gender, level of rowing performance, equipment, and protocol dierences between these and the present study make comparisons dicult.…”
Section: Discussionmentioning
confidence: 99%
“…This test is a standard criterion used at national team selection camps in a number of countries (Kramer et al 1994), and was familiar to all of the subjects in this study. The test is designed to simulate the duration, intensity and stroke rating of an actual 2-km race on the water, and each rower was instructed to use her normal race strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Competitive Olympic rowing is regarded as an endurance sport and there is a close relationship between rowing performance and rowers' aerobic capacity (Cosgrove et al 1999;Kramer et al 1994;Yoshiga and Higuchi 2003). Rowing performance is dependent upon the functional capacity of both aerobic and anaerobic energy pathways (Secher 1973), with the amount of energy derived from anaerobic metabolism amounting to 21-30% (Secher 1993), and 70-86% from aerobic metabolism (Messonnier et al 1997).…”
Section: Introductionmentioning
confidence: 99%